The HSA21 gene EURL/C21ORF91 controls neurogenesis within the cerebral cortex and is implicated in the pathogenesis of Down Syndrome - Li, S.; Qu, Z.; Haas, M.; Ngo, L.; Heo, Y.; Kang, H.; Britto, J.; Cullen, H.; Vanyai, H.; Tan, S.; Chan-Ling, T.; Gunnersen, J.; et al. (Nature Publishing Group, 2016)
Copy number variations to chromosome 21 (HSA21) cause intellectual disability and Down Syndrome, but our understanding of the HSA21 genetic factors which contribute to fetal brain development remains incomplete. Here, we focussed on the neurodevelopmental functions for EURL (also known as C21ORF91, Refseq Gene ID:54149), a protein-coding gene at the centromeric boundary of the Down Syndrome Critical Region (DSCR) of HSA21. We report that EURL is expressed during human and mouse cerebral cortex development, and we report that alterations to EURL mRNA levels within the human brain underlie Down Syndrome. Our gene perturbation studies in mice demonstrate that disruptions to Eurl impair progenitor proliferation and neuronal differentiation. Also, we find that disruptions to Eurl impair the long-term positioning and dendritic spine densities of cortical projection neurons. We provide evidence that EURL interacts with the coiled-coil domain-containing protein CCDC85B so as to modulate ß-catenin levels in cells. Further, we utilised a fluorescent reporter (8xTOPFLASHd2EGFP) to demonstrate that disruptions to Eurl alter ß-catenin signalling in vitro as well as in vivo. Together, these studies highlight EURL as an important new player in neuronal development that is likely to impact on the neuropathogenesis of HSA21-related disorders including Down Syndrome.